2017
DOI: 10.3762/bjnano.8.186
|View full text |Cite
|
Sign up to set email alerts
|

Optical techniques for cervical neoplasia detection

Abstract: This paper provides an overview of the current research in the field of optical techniques for cervical neoplasia detection and covers a wide range of the existing and emerging technologies. Using colposcopy, a visual inspection of the uterine cervix with a colposcope (a binocular microscope with 3- to 15-fold magnification), has proven to be an efficient approach for the detection of invasive cancer. Nevertheless, the development of a reliable and cost-effective technique for the identification of precancerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 141 publications
(145 reference statements)
0
55
0
Order By: Relevance
“…34 OCT has a special potential in gynecologic applications due to high-resolution imaging, customized probes, and sensitivity to both morphologic and functional changes. 63,71,72 The main advantages of applications of OCT technology in gynecology are noninvasiveness and ease of operation; generally, its usage is similar to that of US technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 OCT has a special potential in gynecologic applications due to high-resolution imaging, customized probes, and sensitivity to both morphologic and functional changes. 63,71,72 The main advantages of applications of OCT technology in gynecology are noninvasiveness and ease of operation; generally, its usage is similar to that of US technology.…”
Section: Resultsmentioning
confidence: 99%
“…OCT has extremely high potential as an efficient solution for this problem. 34 The first clinical experience of OCT application for cervix diagnostic was gained in 1997 16 when typical OCT images of cervical tissue in norm and neoplasia were obtained. It was demonstrated that the OCT images of cervix in norm feature stratified squamous cell epithelium and connective tissue stroma with vessels, while a structureless image is an indicator of neoplasia.…”
Section: Optical Coherence Tomography Diagnostics Of Cervixmentioning
confidence: 99%
“…Various imaging techniques, primarily based on transmission, absorption, reflection, spontaneous emission and scattering in light‐tissue interactions, have shown to be responsive to a number of subtle alterations in various diseased tissue. Mueller matrix (MM) polarimetric imaging based on the acquisition of 16 images has shown tremendous potential in precancer detection since the last decade and is best suited for a complete characterization of the biological specimen . These MM images are further processed to extract the essential optical parameters, namely, diattenuation, retardation and depolarization through Lu‐Chipman decomposition method .…”
Section: Introductionmentioning
confidence: 99%
“…due to inflammation, tumor growth, etc. Therefore, the physical parameters, which quantitatively define these changes, are considered as valuable markers for the diagnostic purpose [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most of modern polarimetric imaging systems [7][8][9][10][11] present the measured Mueller matrix data in form of two-dimensional (m × n) distributions of matrix elements, known also as Mueller matrix images (MMI) and denoted here as q(m × n).…”
Section: Introductionmentioning
confidence: 99%